Pengaruh Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Kabupaten Batang Hari Tahun 2010-2020 - Budi Darma; Kasiyati Yunita Wulansari (J-MAS (Jurnal Manajemen dan Sains), 2021)
This research discusses the influence of population on the economic growth of Batang Hari Regency in 2010-2020. Variable population as the independent variable, and the variable economic growth as the dependent variable. The population has a role in various economic activities. Not only on the production side, the population also affects the level of consumption of an item which can have an impact on the economic growth of a region. To determine the influence of population on the economic growth of Batang Hari Regency in 2010-2020, a simple linear regression analysis tool was used with the application of the t test with the aim of knowing whether the population variable had a partial effect or not on the economic growth variable. After processing the data and analyzing it, it can be concluded that based on the results of the t test, the population variable has a partial (partial) influence on economic growth. From the coefficient of determination, the Adjusted R Square value is 0.708. This means that the population affects economic growth by 70.8%. While 29.2% is influenced by other variables that are not discussed in this study.